Development of E-Flashcard Vocabulary on I Like Fruits as a Learning Media Assisted by Heyzine Flipbook - Setiyaningsih, Indri; Adiwijaya, Pande Agus; Numertayasa, I Wayan (research, training and philanthropy institution Natural Aceh, 2024)
This study aims to determine the needs of teachers in the process of implementing learning in 1st-grade elementary school and to develop e-flashcard vocabulary on I Like Fruits material as a learning media assisted by Heyzine flipbook. This level 1 development research design refers to the development research design described by Sugiyono, which includes research and information gathering, planning, developing the initial form of the product, initial field trials, and revising the main product. The subject of this research is a first-grade English teacher. The object of development is vocabulary e-flashcards for first-grade students of SD Negeri 2 Mas. The validation was conducted by an expert who is a lecturer at the Institute of Technology and Education, Markandeya Bali, and an English teacher at SD Negeri 2 Mas. The validation level of vocabulary e-flashcards was analyzed with descriptive statistics using a Likert scale. The results obtained on the e-flashcard vocabulary material I Like Fruits grade one elementary school obtained very valid results with an average score of 4.91. The results of the first expert assessment amounted to 4.85, the results of the second expert assessment amounted to 4.96, and the results of the third expert assessment amounted to 4.96 from the predetermined interval scale. The implications of this study focus on the use of e-flashcard learning media to improve efficiency and adaptability, thus increasing the effectiveness of the e-flashcard learning method.